Heat transfer enhancement in cryogenic quenching process - Chung, J. N. (Int J Therm Sci, 2019)
This paper reports a heat transfer advancement in the cryogenic quenching process. An experiment was performed to evaluate the enhancement of quenching heat transfer by the use of metal tubes with low thermal conductivity coating layers. Four coating thicknesses with various coolant mass flow rates of liquid nitrogen were investigated. The results indicated that the tube inner surface coating greatly enhanced the quenching efficiency. The quenching efficiency was found to increase with increasing number of coating layers, and the efficiency also increased with decreasing mass flow rates. In general, the efficiencies cover a range between 40.6% and 80%. Comparing to the bare surface case, the percentage increase in the quenching efficiency was the minimum at 4.2% for a single coated layer at the highest flow rate and the maximum of 109.1% for four coated layers at the lowest flow rate. The coated tubes could save up to 53% in the amount of cryogen consumption.